Coordinated regulation of propionyl-CoA carboxylase subunits drives precursor flux optimization in spinosad production - Xia, Ziyuan; Li, Xiaomin; Liu, Xirong; Cao, Li; Jin, Duo; Dai, Zirui; Bai, Baolong; Liu, Qian; Rang, Jie; Zhu, Zirong; Xia, Liqiu (Frontiers in Microbiology, 2025)
Spinosad, a natural agricultural pesticide produced by Saccharopolyspora spinosa, has gained global attention owing to its potent insecticidal properties and environmental compatibility. To enhance spinosad biosynthesis, the propionyl-CoA carboxylase (PCC) complex responsible for precursor synthesis was investigated in this study. Six engineered strains were constructed using clustered regularly interspaced short palindromic repeats interference (CRISPRi) and overexpression strategies to systematically regulate the core PCC subunits encoded by pccA, pccB1, and pccB2. Upregulation of these genes enhanced PCC activity, improved energy and precursor utilization, and activated metabolic pathways, ultimately leading to increased spinosad production. Contrary to expectations, CRISPRi-mediated suppression of pccB1 resulted in the highest-yielding strain, demonstrating a 2.6-fold increase in production over the wild type. Integrated quantitative reverse transcription-polymerase chain reaction, heterologous expression, western blot, and proteomic analyses revealed compensatory regulation within the PCC family. pccB1 downregulation significantly upregulated pccA and pccB2 expression while enhancing PCC enzymatic activity. Subsequent proteome-guided supplementation of amino acids critical for spinosad precursor synthesis augmented the yields. The optimized S. spinosa-pSET-dCas9-pccB1 strain, supplemented with alanine, achieved a remarkable 6.2-fold increase in production compared with the parental strain, establishing an effective strategy for metabolic engineering of spinosad biosynthesis.